The Government's Role in Stabilizing Rice Prices in Central Sulawesi - Wardana, Andy; Yunus, Rabina; Syamsu, Suhardiman (Journal La Bisecoman, 2023)
This research aims to find out the government's role in stabilizing rice prices. This research focuses on what things are being done by the government, in this case Perum Bulog and Disperindag, Central Sulawesi to reduce the increase in rice prices. The method used is qualitative. Collection uses observation, interviews, documents and internet searching. The location of this research includes the city of Palu, Kab. Parigi Moutong, Kab. Donggala, and Kab. Sigi. The theory used is the role of government in the economy based on its activities which consist of the role of government as regulator, producer and consumer. The results of the research show that the government's role is not optimal, it can be seen from the government's role as a regulator, to implement various policies and programs, the government has a basis, namely the government purchasing price (HPP) and the highest retail price (HET), which then created the SPHP rice program by Bulog and cheap market by Disperindag. The role of the government as a producer, the government has constraints or problems with the amount of rice stock, the lack of stock it has means that the efforts made do not run optimally so that it has not been able to stabilize or withstand the increase in rice prices. The role of the government as a consumer, the government has difficulty absorbing local rice and imported rice, HPP regulations seem to make it difficult for the government because prices at the milled farmer level are high above HPP and importing countries impose export restrictions and some even stock exports.